Pengaruh Gaya Kepemimpinan Transformasional Terhadap Kinerja Karyawan - Rahman, Repin Ali; Tiorida, Ermina (POLITEKNIK NEGERI BANDUNG, 2016)
The style of leadership is an important element in a business organization. Leadership style described by Bass consists of transformational leadership and transactional leadership. This study aims to determine how well the transformational leadership style towards employee performance in Kamojang Green Hotel & Resort, in addition to this study, aims to determine the relationship between leadership style with employee performance employee in Kamojang Green Hotel & Resort. This study uses qualitative methods with data collection through questionnaires distributed randomly to employees who work in Kamojang Green Hotel & Resort. The phenomenon happens in Kamojang Green Hotel & Resort is a high level of employee come late due to lack of supervision of the leaders and the lack of punishment that makes a deterrent to employees.To achieve the objectives that have been outlined previously, researchers used several tests such as the test statistic descriptive analysis, correlation, regression and the coefficient of determination. The result is a style of leadership transformational and employees in Kamojang Green Hotel & Resort is good, style of leadership significant positive effect on employee performance, Y = 3,529+0,231???????? a regression coefficient after regression testing against the influence of transformational leadership style on employee performance in Kamojang Green Hotel & Resort.